Bankacılık riskleri kapsamında katılım bankacılığında operasyonel riskler ve ekonomik analizi - Ercankal, Recep Ragıp (My University, 2019)
ÖZETBankacılık sektörü riskleri; dar anlamda, kredi riski, likidite riski, faiz oranı riski, döviz kuru riski, piyasa riski ve operasyonel risklerdir. Süre gelen ekonomik gelişmeler, bütünleşen uluslararası piyasalar, mali küreselleşme belirsizliği artırmış ve değişen dünya koşulları ile birlikte ihtiyaçlar ve eksiklikler görülmüş; gerek personel, gerekse de teknolojik ve sistem kaynaklı gelişen operasyonel risklerin artan önemi anlaşılmıştır. Buna yönelik Basel düzenlemeleri ile birlikte operasyonel risklerinölçümüne yönelik kalitatif ve kantitatif yaklaşımlar geliştirilmiş ve detaylandırılmıştır.Diğer taraftan, gerek fon toplama yöntemleriyle, gerekse de fon kullandırma yöntemleriyle konvansiyonel bankacılıktan ayrışan katılım bankacılığı (İslâmi bankacılık), hem ülkemizde hem de dünyada gelişmekte, reel ekonomiyi finanse ederek krizlere karşı daha dirençli yapıyı oluşturmaktadır. Buna karşılık kendine özgü riskler de barındıran katılım bankacılığında operasyonel riskler de yadsınamayacak boyuttadır. Bu çalışmanın amacı operasyonel riskleri katılım bankacılığı özelinde ele almak ve geleneksel bankacılıktan farklarını incelemektir.

OPERATIONAL RISKS AND IT'S ECONOMIC ANALYSISIN PARTICIPATION BANKING IN THE CONTEXT OF BANKING RISKSABSTRACTBanking sector risks; In the narrow sense, credit risk, liquidity risk, interest rate risk, exchange rate risk, market risk and operational risks. Ongoing economic developments, integrated international markets, financial globalization have increased uncertainty and needs and shortcomings have been observed along with changing world conditions; The increasing importance of operational risks arising from both personnel and technological and system-related developments has been understood. Together with the Basel regulations, qualitative and quantitative approaches to the measurement of operational risks have been developed and detailed.In addition, participation banking (Islamic banking), which distinguishes itself from conventional banking by means of fund-collection methods and fund-raising methods, both develops in our country and in the world and creates a more resistant structure against crises by financing in real economy. On the other hand, operational risks in participation banking, which also have specific risks, are also negligible. The aim of this study is to examine operational risks in the context of participation banking and to examine their differences from conventional banking.
Keywords: Bankacılık; Bankacılık Riskleri; Banking; Banking Risks; Islamic Banking; İslami Bankacılık; Katılım Bankacılığı; Operasyonel Riskler; Operational Risks; Participation Banking